2009
DOI: 10.3748/wjg.15.4316
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thymidylate synthase and glutathione-s-transferase π in patients with esophageal squamous cell carcinoma

Abstract: AIM:To investigate the expression of thymidylate synthase (TS) and glutathione-s-transferase π (GST-π) in esophageal squamous cell carcinoma and their association with the clinicopathologic characteristics. METHODS:Immunohistochemical methods were used to detect the expression of TS and GST-π in surgically resected formalin-fixed, paraffin-embedded esophageal squamous cell carcinoma (ESCC) tissue sections from 102 patients (median age, 58 years) and in 28 normal esophageal mucosa (NEM) samples. The relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In contrast, low HO-1 expression is associated with lymph node metastasis in tongue SCC [26]. In esophageal SCC, the levels of GST expression in well-diVerentiated SCC are higher than those in poorly diVerentiated SCC [8]. The present study shows that a group of phase 2 enzymes are up-regulated in relation to the degree of cell diVerentiation in normal KC or SCC.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, low HO-1 expression is associated with lymph node metastasis in tongue SCC [26]. In esophageal SCC, the levels of GST expression in well-diVerentiated SCC are higher than those in poorly diVerentiated SCC [8]. The present study shows that a group of phase 2 enzymes are up-regulated in relation to the degree of cell diVerentiation in normal KC or SCC.…”
Section: Discussionmentioning
confidence: 60%
“…At the cellular level TS expression was observed both in the nucleus and the cytoplasm. In the literature, variations are observed in scoring for TS: nuclear [20], cytoplasmic, [19] and both nuclear/cytoplasmic [11]. In our study only the nuclear staining was considered.…”
Section: Methodsmentioning
confidence: 99%
“…In oesophageal cancer, increased TS expression has been recognised to be associated with poor differentiation [11], nonresponse to chemotherapy [12], and tumour recurrence [13]. In gastric cancer TS expression has been studied as a predictive marker of response to chemotherapy [1416] and poor differentiation [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GSTO1, GSTP1 and GST-pi have been recognized as tumor-associated antigens and act as indicators of prognosis in human ESCC. 5 , 6 , 7 Moreover, previous findings have demonstrated that a GSTM1 deletion polymorphism is associated with an increased ESCC risk. 8 In contrast, another study has demonstrated that the GSTM1 non-null genotypes are highly represented in ESCC patients compared with control patients in China.…”
Section: Introductionmentioning
confidence: 98%